Renewal in Canadian Public Sector Unions: Neoliberalism and Union Praxis - Camfield, David (Relations industrielles / Industrial Relations, 2007)
Challenges from employers and governments and the limited success of public sector union responses suggest the need for renewal in Canadian public sector unions. This article engages with discussions of union renewal by way of theoretically conceptualizing the modes of union praxis relevant to Canadian unions. It then examines the nature of neoliberal public sector reform and assesses the experiences of Canadian public sector unions under neoliberalism. In this difficult context, unions that are able to make progress in the interconnected development of greater democracy and power will be more capable of channelling workers’ concerns into union activity. This, along with international and Canadian evidence, highlights the significance of the praxis of social movement unionism to union renewal in the public sector.